2013
DOI: 10.1111/j.1552-6569.2012.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Alterations in Early Stages of Schizophrenia: A Systematic Review of Diffusion Tensor Imaging Studies

Abstract: Several lines of evidence suggest that the normal integration of cerebral communication may be compromised in schizophrenia, with white matter (WM) abnormalities being integral to these functional deficits. Diffusion tensor imaging (DTI) is a neuroimaging technique which has increasingly been used to study WM through quantitative indices of its structural and orientational characteristics. Identifying the WM differences early in the course of schizophrenia may assist in prevention, early diagnosis and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
2
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(158 citation statements)
references
References 143 publications
(758 reference statements)
13
140
2
3
Order By: Relevance
“…Additionally, in Study 1, we observed relatively higher incidences of schizophrenia spectrum disorders in this subgroup, leading us to characterize the impairments observed in Cluster 3 as having a neurodevelopmental etiology (Marenco & Weinberger, 2000). White matter abnormalities are consistently identified early in the course of psychotic illness in key frontal and temporal tracts, including the superior longitudinal fasciculus, cingulum, uncinate fasciculus, and corpus callosum (see for review Samartzis et al, 2014). More recent evidence has suggested that abnormal neurodevelopment of cerebellar-thalamic circuitry in the prodrome is associated with neurological soft signs and negative symptoms (Mittal et al, 2014).…”
Section: Tract-based Spatial Statistics -Whole Brain Approachmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, in Study 1, we observed relatively higher incidences of schizophrenia spectrum disorders in this subgroup, leading us to characterize the impairments observed in Cluster 3 as having a neurodevelopmental etiology (Marenco & Weinberger, 2000). White matter abnormalities are consistently identified early in the course of psychotic illness in key frontal and temporal tracts, including the superior longitudinal fasciculus, cingulum, uncinate fasciculus, and corpus callosum (see for review Samartzis et al, 2014). More recent evidence has suggested that abnormal neurodevelopment of cerebellar-thalamic circuitry in the prodrome is associated with neurological soft signs and negative symptoms (Mittal et al, 2014).…”
Section: Tract-based Spatial Statistics -Whole Brain Approachmentioning
confidence: 91%
“…We selected several major white matter tracts that have projections to frontal and temporal regions including the corpus callosum, cingulum, superior longitudinal fasciculus, and anterior corona radiata. These tracts are commonly examined within the DTI literature and consistently implicated in various clinical conditions such as schizophrenia (Samartzis, Dima, Fusar-Poli, & Kyriakopoulos, 2014), HIV (Leite et al, 2013), and polysubstance abuse (Unterrainer et al, 2015;Willi et al, 2016). Our a priori ROI approach was followed by a whole-brain approach using…”
Section: Objectives and Hypothesesmentioning
confidence: 99%
“…On the other hand, schizophrenia patients may also show white matter disintegrity even in very early stages (9), and some of these white matter changes were also reported to correlate with clinical measures as neurocognitive symptoms and negative symptoms (10,11). However, white matter analysis showed that multiple circuits were involved in the disorder (12), and they may be related to different phenotypes of the disorder or converging functions of these circuits.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have acquired important and useful information that has improved our understanding of the biological basis of schizophrenia and have provided many indices to aid psychiatrists in improving the rates of accurate diagnoses and treatment efficacies [9][10][11][12][13][14][15][16][17]. However, most of these previous studies have focused on exploring the common brain features shared by patients with schizophrenia and depression, these previous studies have provided evidence that structural or functional impairments in some brain regions in patients with schizophrenia overlap with impairments observed in patients with MDD to some extent, The temporal lobe and anterior cingulate are the main affected regions [7,[18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%